1996
DOI: 10.1254/jjp.71.273
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Analysis of the H2O2-Induced Increase in Intracellular Ca2+ Concentration of Rat Thymocytes

Abstract: The effect of hydrogen peroxide (H202) on the intracellular Ca2+ concentration ([Ca 2+]i) of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…These findings suggest that the intracellular Ca 2ϩ is not involved directly in hydrogen peroxide (1 mM)-induced cell death in the resistant cells. Okazaki et al 35) showed that hydrogen peroxide may increase the [Ca 2ϩ ] i through a mechanism related to the effects of hydrogen peroxide on the cellular nonprotein thiol. Accordingly, the elevated level of intracellular GSH in the resistant cells seems to reduce the amount of hydrogen peroxide-induced increase in the intracellular Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the intracellular Ca 2ϩ is not involved directly in hydrogen peroxide (1 mM)-induced cell death in the resistant cells. Okazaki et al 35) showed that hydrogen peroxide may increase the [Ca 2ϩ ] i through a mechanism related to the effects of hydrogen peroxide on the cellular nonprotein thiol. Accordingly, the elevated level of intracellular GSH in the resistant cells seems to reduce the amount of hydrogen peroxide-induced increase in the intracellular Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown in Figs. 3 and 9, the application of 3 mM H202 to the cells also increases [Ca 2+], (4). The sus tained increase in [Ca 2+1, is one of common features in the processes leading to cell death and cell injury (19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no information concerning their protective actions on living cells suffering from the oxidative stress. In this study, we first examined the effects of cassumunins A and B on living cells under oxi dative stress induced by hydrogen peroxide (H202) by using a flow cytometer and ethidium bromide (3)(4)(5) to determine if they exert protective actions on living cells. Secondly, we have compared the potencies of cassumu nins in protecting the cells against the oxidative stress with that of curcumin because curcumin, a compound abun dant in ginger rhizomes, is known to have antioxidant activity (6,7) and its chemical structure is contained in those of cassumunins A and B (see Fig.…”
Section: Abstract-mentioning
confidence: 99%
See 2 more Smart Citations